Diagnosing Premotor Multiple System Atrophy: Natural History and Autonomic Testing in an Autopsy-Confirmed Cohort. (13th September 2022) - Vichayanrat, Ekawat; Valerio, Fernanda; Koay, Shiwen; De Pablo-Fernandez, Eduardo; Panicker, Jalesh; Morris, Huw; Bhatia, Kailash; Chelban, Viorica; Houlden, Henry; Quinn, Niall; Navarro-Otano, Judith; Miki, Yasuo; et al.
Abstract : Background and Objectives: Nonmotor features precede motor symptoms in many patients with multiple system atrophy (MSA). However, little is known about differences between the natural history, progression, and prognostic factors for survival in patients with MSA with nonmotor vs motor presentations. We aimed to compare initial symptoms, disease progression, and clinical features at final evaluation and investigate differences in survival and natural history between patients with MSA with motor and nonmotor presentations. Methods: Medical records of autopsy-confirmed MSA cases at Queen Square Brain Bank who underwent both clinical examination and cardiovascular autonomic testing were identified. Clinical features, age at onset, sex, time from onset to diagnosis, disease duration, autonomic function tests, and plasma noradrenaline levels were evaluated. Results: Forty-seven patients with autopsy-confirmed MSA (age 60 ± 8 years; 28 men) were identified. Time from symptom onset to first autonomic evaluation was 4 ± 2 years, and the disease duration was 7.7 ± 2.2 years. Fifteen (32%) patients presented with nonmotor features including genitourinary dysfunction, orthostatic hypotension, or REM sleep behavior disorder before developing motor involvement (median delay 1–6 years). A third (5/15) were initially diagnosed with pure autonomic failure (PAF) before evolving into MSA. All these patients had normal supine plasma noradrenaline levels (332.0 ± 120.3 pg/mL) with no rise on head-up tilt (0.1 ± 0.3 pg/mL). Patients with MSA with early cardiovascular autonomic dysfunction (within 3 years of symptom onset) had shorter survival compared with those with later onset of cardiovascular autonomic impairment (6.8 years [5.6–7.9] vs 8.5 years [7.9–9.2]; p = 0.026). Patients with early urinary catheterization had shorter survival than those requiring catheterization later (6.2 years [4.6–7.8] vs 8.5 years [7.6–9.4]; p = 0.02). The survival of patients with MSA presenting with motor and nonmotor symptoms did not differ ( p > 0.05). Discussion: Almost one-third of patients with MSA presented with nonmotor features, which could predate motor symptoms by up to 6 years. Cardiovascular autonomic failure and early urinary catheterization were predictors of poorer outcomes. A normal supine plasma noradrenaline level in patients presenting with PAF phenotype is a possible autonomic biomarker indicating later conversion to MSA.